Investigation of indirect excitons in bulk 2H-MoS2 using transmission electron energy-loss spectroscopy. (27th April 2018) - Habenicht, Carsten; Schuster, Roman; Knupfer, Martin; Büchner, Bernd
Abstract: We have investigated indirect excitons in bulk 2H-MoS2 using transmission electron energy-loss spectroscopy. The electron energy-loss spectra were measured for various momentum transfer values parallel to the and directions of the Brillouin zone. The results allowed the identification of the indirect excitons between the valence band K v and conduction band Λc points, the Γv and K c points as well as adjacent K v and points. The energy-momentum dispersions for the K v -Λc, Γv - K c and K v1 - excitons along the line are presented. The former two transitions exhibit a quadratic dispersion which allowed calculating their effective exciton masses based on the effective mass approximation. The K v1 - transition follows a more linear dispersion relationship.